2019
DOI: 10.14245/ns.1938198.099
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Narcotic Use, Impaired Ambulation Status, and Increased Intraoperative Blood Loss Are Independent Risk Factors for Complications Following Posterior Cervical Laminectomy and Fusion Surgery

Abstract: Objective: This retrospective cohort study seeks to identify risk factors associated with complications following posterior cervical laminectomy and fusion (PCLF) surgery. Methods: Adults undergoing PCLF from 2012 through 2018 at a single center were identified. Demographic and radiographic data, surgical characteristics, and complication rates were compared. Multivariate logistic regression models identified independent predictors of complications following surgery. Results: A total of 196 patients met the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…The incidence of surgical site infection in posterior cervical surgery has been reported to be between 3% to 10% [11][12][13][14]. Diabetes has been identified as an independent factor increasing postoperative complications in cervical spine surgery [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of surgical site infection in posterior cervical surgery has been reported to be between 3% to 10% [11][12][13][14]. Diabetes has been identified as an independent factor increasing postoperative complications in cervical spine surgery [15].…”
Section: Discussionmentioning
confidence: 99%
“…The bleeding can be easily controlled with bipolar coagulation and absorbable hemostatic agents. In our microsurgical laboratory, we conducted anatomical dissection studies to identify this corridor and its relationship with the vertebral artery for the screw insertion point as shown in Figure 1B [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Some complications may eventually lead to deadly diseases, such as pulmonary embolism resulting from deep vein thrombosis and sepsis from pressure ulcers. Postoperative ambulation is a significant predictor of patients not developing complications 26 . In the current study, early ambulation showed favorable results, with patients in the EA group having 69.8% lower incidence of urinary retention, and no patients had ileus.…”
Section: Early Ambulation Decrease Postoperative Pain Levelmentioning
confidence: 99%
“…14 Significant intraoperative blood loss (SIBL), which was defined as intraoperative blood loss of 500 mL or more, may result in hypotension, hypoxia of tissues and organs, and nerve ischemic injury, thus increasing the recovery time and the morbidity and complication rates. [15][16][17][18] Several surgical and patient factors, such as female sex, low preoperative hemoglobin levels, higher American Society of Anesthesiologists (ASA) classification, longer operative time, lower body mass index (BMI), smoking and older age, may contribute to perioperative blood loss. [19][20][21][22][23][24] SIBL during cervical laminoplasty, especially for OPLL, may result in more neurologic complications, worse neurologic recovery, and longer length of stay.…”
Section: Introductionmentioning
confidence: 99%